Respuesta :

1)
11x+5y=20
2x+5y=-25

multiply the second equation by - 1 and add the result with the first equation:

11x + 5y = 20
- 2x - 5y = 25
-------------------
9x = 45

=> x = 45 / 9

=> x = 5

Replace in
2x+5y=-25

=> 2(5) + 5y = - 25

5y = - 25 - 10

5y = - 35

y = - 35 / 5

y = - 7


2)

3x+7y=-21

3x-7y=63


Add the two equations:

3x + 3x + 0 = - 21 + 63

6x = 42

=> x = 42 / 6

=> x = 7

Replace in 3x-7y=63

3(7) - 7y = 63

=> 7y = 21 - 63

=-> 7y = - 42

=> y = - 42 / 6

=> y = - 7